Assessment of Adverse Events and Predictors of Neurological Recovery After Therapeutic Hypothermia. (January 2014) - MacLaren, Robert; Gallagher, Jolie; Shin, John; Varnado, Sara; Nguyen, Lam
Background: Therapeutic hypothermia improves neurological recovery after witnessed cardiac arrest from ventricular fibrillation or tachycardia. Its application is expanding despite associated adverse events.Objective: To assess the occurrence of adverse events and predictors of good versus poor neurological recovery after therapeutic hypothermia.Methods: A single-center, retrospective review of medical records of 91 patients who received therapeutic hypothermia for ≥6 hours. Adverse events included laboratory abnormalities, shivering, acute kidney injury, or infection. Cerebral performance categories (CPC) scores delineated good (CPC of 1-3) or poor (CPC of 4 or 5) neurological outcomes. Groups were compared and parameters evaluated for effect on neurological recovery using backward logistic regression analysis.Results: Therapeutic hypothermia was used for several indications, and 42 patients (46.2%) had good neurological recovery. Demographic parameters were similar between groups. Common adverse events were hypoglycemia (98.9%), shivering (84.6%), bradycardia (58.2%), electrolyte abnormalities (26.4%-91.2%), acute kidney injury (52.8%), infection (48.4%), and coagulopathy (40.7%). Characteristics independently associated with neurological recovery included faster return of spontaneous circulation (ROSC), quicker initiation of cooling, and the occurrence of infections. Pulseless electrical activity, faster achievement of goal cooling temperature, seizure, and the administration of insulin or epinephrine were inversely related to neurological recovery.Conclusions: Adverse events of therapeutic hypothermia were numerous and frequent, necessitating monitoring. Neurological recovery is primarily driven by the type of arrest, the rapidity of ROSC, the time needed to provide and achieve therapeutic hypothermia, the development of seizures or infection, and the use of insulin or epinephrine.